Bio-template synthesis of CeO2 ultrathin nanosheets for highly selective and sensitive detection of ppb-level p-xylene vapor. Issue 2 (15th January 2022) - Liu, Jing-Shuo; Zhen, Yan-Xue; Zhang, Xian-Fa; Deng, Zhao-Peng; Xu, Ying-Ming; Huo, Li-Hua; Gao, Shan
Abstract: Highly selective of carcinogenic and flammable p -xylene vapor and its sensing detection through metal oxides-based sensors has recently attracted much attention. In this work, mesoporous CeO2 nanosheets were synthesized by simple cerium nitrate impregnation and air calcination using rose petals as bio-template. The effect of calcination temperature on its microstructure, Ce 3+ /Ce 4+ mole ratio, as well as sensing performance was investigated. The CeO2 -650 ultrathin nanosheets calcined at 650 °C are assembled by cross-linking nanoparticles with small size, which possess homogeneous mesoporous distribution and relatively large specific surface area. At 217 °C, the sensor fabricated from CeO2 -650 ultrathin nanosheets shows short response time ( T res = 5 s), high selectivity and response ( S = 22.1) towards 100 ppm p -xylene vapor, and its limit of detection (30 ppb) is the lowest among reported sensors based on pure metal oxides. The good sensing performance mainly originate from the synergistic effect of intrinsic features of mesoporous CeO2 -650 ultrathin nanosheets, surface adsorbed oxygen control, oxygen vacancy defects induced by Ce 3+ and biotemplate imprinting. Therefore, mesoporous CeO2 -650 ultrathin nanosheets could be utilized as candidate for the detection of trace p -xylene vapor.